A study on customer's perception towards the effectiveness of entrepreneurial training conducted by SIRIM Sabah / Noor Azleen Ahmad - Ahmad, Noor Azleen (2013)
The purpose of this research is to study on customer's perception towards the effectiveness of entrepreneurial training conducted by SIRIM Sabah. SIRIM provided training to help participant to improve their business skills and they can participate in hydro stone training, glass training, foundry training, packaging training and seminar. Thus there were 130 respondents selected by the researcher to be the sample size of this research and a simple convenience sampling technique was used to select the respondents who come to SIRIM Sabah. From the finding of the research the researcher founded that there were many category of customer that participate in SIRIM's Sabah entrepreneurial training program which different in terms of district, age, races, education level, income level and types of training. In addition of that, the researcher also found that there were many training program that SIRIM provide to help customers. Besides that, SIRIM also provide adequate exposure about business to customers and help customer to improve their socioeconomic status. Respondents also have the opportunities to give suggestion on how to improve the quality of the training. Hence the objectives of this research have been achieved.